Regulation of the wild-type and Y1235D mutant Met kinase activation. - Cristiani, C; Rusconi, L; Perego, R; Schiering, N; Kalisz, H; Knapp, S; Isacchi, A (2005)
Met receptor tyrosine kinase plays a crucial role in the regulation of a large number of cellular processes and, when deregulated by overexpression or mutations, leads to tumor growth and invasion. The Y1235D mutation identified in metastases was shown to induce constitutive activation and a motile-invasive phenotype on transduced carcinoma cells. Wild-type Met activation requires phosphorylation of both Y1234 and Y1235 in the activation loop. We mapped the major phosphorylation sites in the kinase domain of a recombinant Met protein and identified the known residues Y1234 and Y1235 as well as a new phosphorylation site at Y1194 in the hinge region. Combining activating and silencing mutations at these sites, we characterized in depth the mechanism of activation of wild-type and mutant Met proteins. We found that the phosphotyrosine mimetic mutation Y1235D is sufficient to confer constitutive kinase activity, which is not influenced by phosphorylation at Y1234. However, the specific activity of this mutant was lower than that observed for fully activated wild-type Met and induced less phosphorylation of Y1349 in the signaling site, indicating that this mutation cannot entirely compensate for a phosphorylated tyrosine at this position. The Y1194F silencing mutation yielded an enzyme that could be activated to a similar extent as the wild type but with significantly slower activation kinetics, underlying the importance of this residue, which is conserved among different tyrosine kinase receptors. Finally, we observed different interactions of wild-type and mutant Met with the inhibitor K252a that may have therapeutic implications for the selective inhibition of this kinase.